A SOTERIOLOGIA SOCIAL DE JOHN WESLEY com consideração especial de seus aspectos comunitários, sinergéticos e públicos - Renders, Helmut (2006)
This study investigates the elements of the soteriology of John Wesley and its dynamic aspects. Instead of favoring a specific period of the life of John Wesley, the theological biography of John Wesley is developed based on the concept of the sedimentation of experience. In this manner, the theologia viatorum of John Wesley is developed with a focus on its transverse elements and their unfolding in terms of communitarian, synergetic and public aspects. According to the thesis, the theologia viatorum of John Wesley gains depth and vitality with its growing and conscious learning from and commitment to the English people, and, in special, with the poor of England. Accompanied by a careful self-analysis, Wesley begins offers an analysis of the diverse soteriologies of his day, which are marked by a slow transition between the Medieval era and modernity. There arises a reconstruction characteristic of soteriology, currently called social soteriology. We understand this social soteriology as a pivotal point in the theology of John Wesley, which manifests itself in a typical soteriological anthropology, Christology, pneumatology, eschatology and ecclesiology. The communitarian, synergetic and public aspects of this social soteriology are seen and developed by Wesley based on his own experience and life with the people, their dynamics, their culture, their needs and their competencies. Such aspects lead, step by step, toward a praxis that begins to contemplate the interconnections between the reform of the Church, the nation and the transformation of persons. This movement is co- motivated by an utopist soteriological horizon that foresees the continuation of the theologia viatorum until the transformation of the entire cosmos. This social soteriology appears as a web that closely accompanies the socio-economic and religious topography of the its time, and seeks paths to overcome impasses, despair, and irresponsibility in relation to the poor.(AU)